Automated deduction -- CADE 27 : 27th international conference on automated deduction, Natal, Brazil, August 27-30, 2019 : proceedings /: 27th international conference on automated deduction, Natal, Brazil, August 27-30, 2019 : proceedings. ([2019]) - Unknown
No abstract available